Identification of CD37, cystatin A, and IL-23A gene expression in association with brain metastasis: analysis of a prospective trial. Issue 1 (March 2019) - Dohm, Ammoren; Su, Jing; McTyre, Emory R.; Taylor, James M.; Miller, Lance D.; Petty, W. Jeffrey; Xing, Fei; Lo, Hui-Wen; Metheny-Barlow, Linda J.; O'Neill, Stacey; Bellinger, Christina; Dotson, Travis; et al.
Purpose/Objectives: We aimed to assess the predictive value of a lung cancer gene panel for the development of brain metastases. Materials/Methods: Between 2011 and 2015, 102 patients with lung cancer were prospectively enrolled in a clinical trial in which a diagnostic fine-needle aspirate was obtained. Gene expression was conducted on all samples that rendered a diagnosis of non-small cell lung cancer (NSCLC). Subsequent retrospective analysis of brain metastases-related outcomes was performed by reviewing patient electronic medical records. A competing risk multivariable regression was performed to estimate the adjusted hazard ratio for the development of brain metastases and non-brain metastases from NSCLC. Results: A total of 49 of 102 patients had died by the last follow-up. Median time of follow-up was 13 months (range 0.23–67 months). A total of 17 patients developed brain metastases. Median survival time after diagnosis of brain metastases was 3.58 months (95% confidence interval (CI) 2.17, not available). A total of 30 patients developed metastases without any evidence of brain metastases until the time of death or last follow-up. Competing risk analysis identified three genes that were downregulated differentially in the patients with brain metastases versus non-brain metastatic disease: CD37 (0.017), cystatin A (0.022), and IL-23A (0.027). Other factors associated with brain metastases include: stage T ( P ⩽ 8.3e -6 ) and stage N ( P = 6.8e -4 ). Conclusions: We have identified three genes, CD37, cystatin A, and IL-23A, for which downregulation of gene expression was associated with a greater propensity for developing brain metastases. Validation of these biomarkers could have implications on surveillance patterns in patients with brain metastases from NSCLC.